Contact : situational supervision for banks - Wells, J. (Reading, Massachusetts ; London : Addison Wesley Pub. Co., 1977)
The purpose of this book is to share with other supervisors, some techniques and methods to establish an ideal supervisory behavior, and to use all of the supervisors' current knowledge and experience in handling today's situation.
Includes bibliographical references: p. 49.
ne 14/03/2019
Loans
Keywords: Supervisors--role and function